ANALISIS DETERMINAN PERILAKU SEKSUAL BERESIKO PADA REMAJA DI SMA LAMPUNG SELATAN TAHUN 2020 - Dewi Rahayu; Novita Lestari; Abikusno Djamaluddin (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2020)
Sexual behavior is said to be risky if the behavior brings unwanted consequences such as abortion, pregnancy outside marriage and Sexually Transmitted Diseases (STDs). In 2019 there were 78 cases of pregnancy and childbirth among adolescents in the working area of ​​Candipuro Health Center. This type of research is quantitative. Analytical research design with cross-sectional approach. The population is all high school students grade X, XI, XII in South Lampung Regency as many as 15,259 students. with a sample of 429 respondents. Data analysis used univariate analysis with percentages, bivariate analysis with Chi Square and multivariate analysis with multiple logistic regression. The results showed that there was a relationship between knowledge with at risk sexual behaviorwith p value 0,001,there was a relationship between attitudes with at risk sexual behaviorwith p value 0,000, there was a relationship betweenimformation sources with at risk sexual behavior with p value 0,002, there was a relationship between friends of the same age with at risk sexual behavior with p value 0,000, there was a relationship the role of parents with at risk sexual behavior with p value 0,017. The dominant factor influencing risky sexual behavior in teens in South Lampung High School in 2020 is attitude with OR 12,064. Efforts that can be made to reduce risky sexual behavior in adolescents by increasing knowledge about reproductive health that can be done through adolescent health care service programs (PKPR) in collaboration with puskesmas.